Sociodemographic disparities in diabetic retinopathy: Analysis of the 2021 behavioral risk factor surveillance system - Dawsyn Smith; S. Mackenzee Hester; Ryan Emmert; Juliana Bryant; Micah Hartwell (AJO International)
Purpose: To investigate and update the prevalence of diabetic retinopathy (DR) by age, race/ethnicity, sex, socioeconomic status, education, and rurality in the United States. Additionally, we aimed to address a gap in research by investigating the rates of DR among the transgender population. Design: We conducted a cross-sectional study using data from the Behavioral Risk Factor Surveillance System, a phone-based survey conducted in the United States and surrounding territories by the Centers for Disease Control, and assessed the prevalence of DR by various sociodemographic factors. Methods: A sample of 21,905 individuals was drawn from survey data based on self-reported diabetes status. We used X2 tests to evaluate the prevalence of DR across sociodemographic factors, and a multivariable logistic regression model with all variables was used to determine adjusted odds ratios as a measure for sociodemographic associations. Results: From the 21,905 participants, the prevalence of DR was lower in females (17.34 %) than males (20.14 %), though highest in transgender participants (27.16 %; P = 0.017). White individuals had the lowest prevalence of DR (16.57 %)—with all other groups exceeding 22 % (P<0.01). DR prevalence was inversely associated with income and educational attainment (P<0.01). The adjusted regression model shoowed significantly higher likelihoods for males (AOR = 1.33; 95%CI: 1.16-1.52) compared to females and for all racial groups compared to White individuals, with Asian Americans showing the highest odds (AOR = 2.08; 95%CI: 1.16-3.71). It also revealed lower odds with increasing income--those earning >$200,000 or more (AOR = 0.40; 95 % CI: 0.22 0.75)—and higher education, with college or technical school graduates (AOR = 0.74; 95 % CI: 0.58–0.95) compared to the lowest levels. Conclusions: Our findings showed higher DR prevalence among all ethnoracial groups, males and transgender individuals, and lower income and education status. These disparities highlight the need for targeted screening and prevention efforts, including removing barriers and improving access to care and community education programs.